Employers’ attitudes to HOU postgraduates’ qualities and skills - Minh Tuyet Hoang (AAOU Journal, 2019)
Purpose - The purpose of this paper is to investigate employers’ attitudes towards qualities and skills for the twenty-first century of Hanoi Open University (HOU) postgraduates. More specifically, it is to find out employers’ assessment and satisfaction on five sets of skills: foundation skills, professional competencies, personal attributes, organizational skills and technical knowledge and skills. Design/methodology/approach - The study used a survey questionnaire as a tool to collect data. The survey was conducted on employers of HOU postgraduates who graduated during the academic years 2015–2016 from five faculties at HOU. Findings - The findings of the study show that employers highly appreciated HOU postgraduates in numeracy skills, ICT literacy skills and information literacy within foundation skills; critical thinking and problem solving skills, collaboration skills and conceptual skills within professional competencies; responsible, integrity and interpersonal skills within organization skills; productivity, organization and planning and time management within organizational skills; knowledge-related regulations and policies at workplace, capacity to use knowledge and skills at workplace and lifelong learning within technical knowledge and skills. Originality/value - The values of the study are that the employer attitudes identified can be used to evaluate educational programs and can be used as a quality assurance measure. The study helps to indicate the gap between the expectation and the satisfaction of employers on HOU postgraduates. Thereby, suggestions can be given to HOU’s management to improve the services at the university in general and the services to postgraduate students in particular to upgrade their qualities and skills to meet social demands.